(untitled) (Research, Society and Development, 2021)
This study aimed to assess the incidence of reported cases of women infected with syphilis during pregnancy and who lived in the Northeast region of Brazil, in the period 2013-2020. It was an epidemiological, cross-sectional and descriptive research that used data obtained from the Notifiable Disclosure Information System (Sistema de Informação de Agravo de Notificação), available on the electronic platform of the Informatics Department of the Unified Health System (Departamento de Informática do Sistema Único de Saúde). Between 2013 and 2020, 63,908 cases of gestational syphilis were reported in the Northeast region of the country, with 2018 having the highest number of cases. It was found that syphilis had a higher number in young pregnant women, between 20-29 years old, brown in color and with low education, which revealed that the disease affects mainly the most vulnerable populations, with reduced access to health, education and information. The lower occurrence happened to women ager over 40, indigenous and yellow skin women and those with higher graduation degree. The Ministry of Health has been evolving in the control of gestational syphilis, creating strategies to strengthen health care networks, and this commitment is perceived from the year 2019, with the significant drop in notifications compared to previous years. And this effort needs to be maintained, with the help of the entire population, so that not only the Northeast region, but the whole of Brazil is able to control and increasingly reduce the incidence of this disease in pregnant women.